Involvement of Ovarian Estradiol Biosynthesis and Pituitary FSH Expression in the Mechanism of Human Chorionic Gonadotropin Stimulation of Uterine Growth in Immature Female Rats. (21st February 2016) - Rafert, Sandrine; Mariot, Julie; Klett, Danièle; Combarnous, Yves
Abstract : In a previous work, we showed that human Chorionic Gonadotropin (hCG) alone is able to stimulate uterine ponderal growth in immature female rats. In the present paper, we provide new information indicating that a single 100 ng hCG injection increased ovarian androgen availability and aromatase activity. These changes are consistent with an increase in ovarian estradiol secretion. Ovarian activin β A and activin β B subunit RNAs expression were also increased following hCG injection. Most interestingly, this treatment also led to an increase in FSH β subunit mRNA expression in the pituitary, which might be due to hCG-stimulated ovarian activin secretion. We have not been able so far to follow the kinetics of the plasma concentrations of activin and FSH in hCG-treated animals compared to control animals. This has to be explored in the future to provide a more complete assessment of our model.